Diffuse cutaneous mastocytosis treated with systemic corticosteroids: a rare case report. - Katakam, B.K.; Gurram, N.R.N.; Chintagunta, S.R.; Dhabal, A. (European Journal of Pediatric Dermatology, 2023)
Diffuse cutaneous mastocytosis is the rarest form of mastocytosis. It usually appears in children and is usually characterized by a leather-like thickening of the skin; marked dermographism or numerous blisters may also be present. In children, diffuse cutaneous mastocytosis tends to regress spontaneously, like the more frequent forms of mastocytoma and maculo-papular mastocytosis, but the higher the risk of systemic complications. Here was reported the case of a 2-month-old girl who initially manifested bullous lesions fol-lowed by generalized orange peel plaques.